Species composition and taxonomic structure of Assassin bugs (Heteroptera: Reduviidae) in Southern Uzbekistan, with the first record of Nagusta goedelii - MAFTUNA VALIEVA; GULNORA MIRZAEVA; DILSHOD MUSAEV; BAKHTIYOR KHOLMATOV; VOKHIDJON AKHMEDOV; SARDORBEK KIMYONAZAROV; MARIFAT HUDOYBERDIEVA; BEKZOD ESHKUVVATOV; SANJAR USANOV; AZIZA KHOLMIRZAYEVA; JASUR KUDRATOV (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Valieva M, Mirzaeva G, Musaev D, Kholmatov B, Akhmedov V, Kimyonazarov S, Hudoyberdieva M, Eshkuvvatov B, Usanov S, Kholmirzayeva A, Kudratov J. 2026. Species composition and taxonomic structure of assassin bugs (Heteroptera: Reduviidae) in Southern Uzbekistan, with the first record of Nagusta goedelii. Biodiversitas 27 (3): d270331. https://doi.org/10.13057/biodiv/d270331. As climate change and urbanization intensify, it is of great importance to determine the systematic structure and diversity of the fauna of natural landscapes that are being degraded. This study presents a comprehensive analysis of the species composition and taxonomic structure of the family Reduviidae (Heteroptera) in Southern Uzbekistan. Based on 162 specimens collected between 2021 and 2024 across four distinct ecological zones (Yakkabog, Sherabad, Nishon, and Termez), a total of 18 species belonging to 12 genera and 5 subfamilies were identified. Sampling was standardized using sweeping, pitfall traps, and light-traps to ensure comparability across different altitudes (800-1300 m asl) and land-use intensities. The subfamily Harpactorinae exhibited the highest diversity (6 species), followed by Reduviinae (5 species) and Stenopodainae (4 species). A major highlight of the study is the first formal record of Nagusta goedelii for the fauna of Uzbekistan. The identification of this species was validated through a detailed morphological diagnosis, focusing on key characters such as the prominent post-antennal spines, elongated "neck" structure, and pronotal tubercles, as well as molecular-genetic analysis. Cytochrome Oxidase I (COI) gene sequencing (PX588124.1) and subsequent phylogenetic reconstruction using Maximum Likelihood supported the distinct placement of the Uzbek specimen within the Nagusta-Serendiba clade (bootstrap 89-100%). Comparative faunal analysis using Jaccard and Sørensen-Dice coefficients revealed significant regional differentiation. A complete faunal turnover (Cj:0.0) was observed between the mountainous habitats of Yakkabog and the arid lowland zones of Nishon, reflecting the impact of environmental filtering. These findings significantly expand the known distribution of Palearctic reduviids and provide a baseline for future biogeographic and ecological monitoring in Central Asia.